1991
DOI: 10.1152/ajpheart.1991.260.6.h1852
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase and oxygen radicals: synergism in lung injury after hindlimb ischemia

Abstract: Hindlimb ischemia and reperfusion lead to lung injury dependent on activated polymorphonuclear neutrophils (PMN) adherence. This study tests whether elastase and oxygen radicals participate in PMN-induced injury once they have become sequestered in lungs. Anesthetized rats treated with saline (n = 9) or the specific elastase inhibitor methoxysuccinyl-L-Ala-L-Ala-L-Pro-L-Val-chloromethylketone (MAAPV, n = 6) underwent 4 h of bilateral hindlimb tourniquet ischemia followed by 4 h of reperfusion. At this time, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1
5

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
2
30
1
5
Order By: Relevance
“…Reperfusion injury is characterized by leukocyte recruitment resulting in tissue dysfunction in various organ systems including heart, skeletal muscle, lungs, intestine, and skin (20)(21)(22)(23)(24). Leukocyte-endothelium interaction involves initial rolling (repeated transient contacts) of leukocytes along the endothelial surface followed by their firm adhesion and diapedesis.…”
mentioning
confidence: 99%
“…Reperfusion injury is characterized by leukocyte recruitment resulting in tissue dysfunction in various organ systems including heart, skeletal muscle, lungs, intestine, and skin (20)(21)(22)(23)(24). Leukocyte-endothelium interaction involves initial rolling (repeated transient contacts) of leukocytes along the endothelial surface followed by their firm adhesion and diapedesis.…”
mentioning
confidence: 99%
“…Infiltrating leukocytes have been implicated as key mediators of ischemia/reperfusion injury associated with the heart (1, 2), brain (3), intestine (4,5), skeletal muscle (6), and various other tissues (7)(8)(9). This contention is based primarily on three pieces of evidence; (a) leukocytes infiltrate postischemic tissue (1, 2, 5), (b) leukocyte depletion from the circulation reduces reperfusion-induced tissue injury (2,4), and (c) reagents that interfere with leukocyte infiltration into postischemic vessels concomitantly provide protection against reperfusion injury (7,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise role of neutrophil elastase in the early stage of the acute lung inflammation has not yet been evaluated. In previous studies of specific elastase inhibitors in several models of lung inflammation, endotoxin was found to cause endothelial cell injury and was almost completely inhibited by elastase inhibitors [16][17][18]. Furthermore, GOSSAGE et al [24] have shown that the synthetic neutrophil elastase inhibitors SC-37698 and SC-39026 reduce endotoxin-induced lung dysfunction in sheep [24].…”
mentioning
confidence: 99%
“…Thus, neutrophils appear to play a major role in LPS-induced lung inflammation [13][14][15]. Most previous studies of proteinase involvement in lung inflammation have focused on neutrophil elastase [16][17][18][19][20][21], since neutrophil elastase is prominent in the BAL fluid of such patients [22,23]. However, the precise role of neutrophil elastase in the early stage of the acute lung inflammation has not yet been evaluated.…”
mentioning
confidence: 99%